2023
DOI: 10.1111/jcmm.17825
|View full text |Cite
|
Sign up to set email alerts
|

GP‐2250, a novel anticancer agent, inhibits the energy metabolism, activates AMP‐Kinase and impairs the NF‐kB pathway in pancreatic cancer cells

Britta Majchrzak‐Stiller,
Marie Buchholz,
Ilka Peters
et al.

Abstract: The oxathiazinane compound GP-2250 (Figure 1A) is a highly effective antineoplastic agent, as has been demonstrated for pancreatic adenocarcinoma in vitro and in vivo. 1,2 GP-2250 inhibited tumour cell proliferation and induced apoptotic cytotoxicity. In vivo, the growth of patient-derived pancreatic tumour tissue was strongly inhibited in xenograft mouse models. 1,2 GP-2250 is presently in a clinical trial for the treatment of pancreatic cancer (NCT 03854110). 3 Its molecular mechanism of action, however, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 29 GP-2250 has been shown in preclinical models to inhibit glyceraldehyde-3-phosphate dehydrogenase, thus limiting aerobic glycolysis, and selectively inducing oxidative stress, mitochondrial dysfunction, and apoptosis. 30 When combined with gemcitabine, the drugs act synergistically in a dose-dependent manner. The open-label phase 1/2 trial of GP-2250 with gemcitabine is underway in patients with advanced unresectable or mPDAC who have progressed on prior FOLFIRINOX.…”
Section: Approaches To Second-line Therapeuticsmentioning
confidence: 99%
“… 29 GP-2250 has been shown in preclinical models to inhibit glyceraldehyde-3-phosphate dehydrogenase, thus limiting aerobic glycolysis, and selectively inducing oxidative stress, mitochondrial dysfunction, and apoptosis. 30 When combined with gemcitabine, the drugs act synergistically in a dose-dependent manner. The open-label phase 1/2 trial of GP-2250 with gemcitabine is underway in patients with advanced unresectable or mPDAC who have progressed on prior FOLFIRINOX.…”
Section: Approaches To Second-line Therapeuticsmentioning
confidence: 99%
“…GP-2250 (Figure 1) is a relatively novel anti-neoplastic substance that has recently been investigated in different cancers [13][14][15][16]. The substance is an oxathiazinane (tetrahydro-1,4,5-oxathiazin-4,4-dioxide) and has inhibitory effects on glyceraldehyde 3-phosphate dehydrogenase (GAPDH) expression and activity, selectively resulting in oxidative stress, mitochondrial dysfunction, and programmed cell death in cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in in vitro as well as in vivo experiments, GP-2250 is able to downregulate the viability of pancreatic carcinoma cells, which is also accompanied by the induction of apoptosis as well as necrosis. The same study group reported on the anti-tumor activity of GP-2250, investigating other malignancies as well [13][14][15][16]. Importantly, the substance proved to be safe in nude mice, indicated by acute or chronic toxicity only at extremely high concentrations (acute toxicity at 2000 mg/kg*BW and chronic toxicity at concentrations higher than 1000 mg/kg*BW in nude mice).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation